COMPREHENSIBLE INPUT, EXPLICIT TEACHING, AND CORRECTIVE FEEDBACK IN GENRE BASED APPROACH TO TEACHING SPOKEN HORTATORY EXPOSITION TEXT - Yustika Nur Fajriah (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This study aims to investigate how effective comprehesible input, explicit teaching and corrective feedback in Genre Based Approach develop students’ speaking in hortatory exposition; particularly in the aspect of genre. To achieve the purpose of the study, a case study design was chosen. The data were collected from classroom observations, and students’ texts. The data from observation were analyzed using four stages of analysis including organizing, transcribing, converting, classifying, describing, and interpreting. The students’ texts were analyzed using the rubric adapted from Butt, Fahey, Feez, spinks, and Yallop (2000) and Emilia (2011).The result confirms that comprehensible input, explicit teaching and corrective feedback develop students’ speaking in hortatory exposition. Students were able to speak by following the genre moves of hortatory exposition. This study suggests that the techniques of comprehensible input, explicit teaching, and corrective feedback are recommended to be applied in a language teaching process.